Genotoxicity of mixtures of glyphosate with 2,4-dichlorophenoxyacetic acid chemical forms towards Cnesterodon decemmaculatus (Pisces, Poeciliidae) - Fernandes Carvalho, Wanessa (2020)
Acute genotoxicity of commercial glyphosate (GLY) (Credit®)-, 2,4-D-acid (2,4-D) (Dedalo Elite)-, 2,4-D-amine (2,4-D DMA) (Weedar Full®)- and 2,4-D-ester (2,4-D BE) (Herbifen Super®)-based herbicide formulations alone and their combinations were analysed in Cnesterodon decemmaculatus. Mortality was evaluated as a lethal end-point and the single cell gel electrophoresis (SCGE) bioassay was used as a sublethal end-point. LC50₉₆ₕ values for Dedalo Elite was 0.46 mg/L and Herbifen Super® was 2.67 mg/L based on 2,4-D and 2,4-D BE, respectively. Results reveal a higher toxicity exerted on C. decemmaculatus after exposure to 2,4-D- rather than 2,4-D BE-based herbicide formulations. Overall, results demonstrated an enhancement in the genetic damage index committed to an enhancement of damaged erythrocytes of C. decemmaculatus when exposed to Credit®, Dedalo Elite, Weedar Full® and Herbifen Super® at 5% and 10% of LC50₉₆ₕ values alone as well as in their combinations. Overall, the combination of GLY plus 2,4-D or GLY plus 2,4-D DMA showed a synergistic pattern whereas the combination of GLY plus 2,4-D BE was antagonic. Furthermore, this research is pioneer in the assessment of lethality and genotoxicity induced by 2,4-D-, 2,4-D DMA- and 2,4-D BE-based formulations when combined with GLY-based formulated herbicides in fish after they are acutely exposed.